ANALISIS PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, CURRENT RATIO, DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM SYARIAH (Studi Kasus pada Perusahaan Yang Terdaftar Dalam Jakarta Islamic Index Periode 2011-2015 ) - Anugrah, Agung; Syaichu, Muhamad (Diponegoro Journal of Management, 2017)
This research aims to determine the influence of variables consisting of Return On Equity, Debt to Equity Ratio, Current Ratio, and privce to Book Value of the stock return of sharia in the companies belonging to the Jakarta Islamic Index (JII) in the year 2007-2011. Sharia stocks are stocks in Jakarta Islamic Index (JII) are corporations stocks while are in operation not contradiction with Islamic Sharia, either on the product or its management. The grouping of Sharia stocks are in Jakarta Islamic Index (JII) in the Jakarta Stock Exchange. This research uses secondary data obtained from the financial statements of companies belonging to the Jakarta Islamic Index (JII). Sampling was done by purposive sampling method, the number of samples used by 14 companies. The analytical method used in this research is multiple linear regression method. The results of this study indicate that the Return On Equity, Debt to Equity Ratio, Current Ratio and Price to Book Value simultaneously significant effect on stock returns. The results of the analysis of partial Return On Equity significant negative effect, while the Debt to Equity Ratio and Price to Book Value significant positive effect, the Current Ratio is not significant positive effect on stock returns. The results showed that 42.7% of variation variable stock returns can be explained by the variable Return On Equity, Debt to Equity Ratio, Current Ratio and Price to Book Value. While 57.3% stock return variable variation explained by other factors.